Carbonaceous reducing agent pellet with low-order non-caking coal as main body and application
By combining low-order viscose-free coal with microsilicon powder and composite organic binder, carbonaceous reducing agent pellets are prepared, which solves the problem of low-order viscose-free coal and microsilicon powder, and achieves efficient utilization of resources and reduce production costs.
Patent Information
- Application Number
- CN202411535345.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
The utilization rate of low-order viscose-free coal and microsilicon powder in the prior art is low, resulting in waste of resources and high production costs.
Low-order non-viscosity coal is used as the main body, combined with microsilicon powder and composite organic binder, and carbonaceous reducing agent pellets are prepared by wet grinding mixing and microwave baking processes.
The fixed carbon content of the pellets, the strength of the pellets and the crushing resistance are improved, and the efficient utilization of low-order viscose-free coal and microsilicon powder is achieved, and the production cost of industrial silicon smelting is reduced.
Smart Images

Figure CN119390072A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbonaceous reducing agent pellet with low-rank non-caking coal as the main body coupled with micro-silicon powder and application thereof, belonging to the technical field of efficient and clean utilization of resources. Background Art
[0002] At present, the production of industrial silicon is mainly carried out by smelting silica and carbonaceous reducing agents in an electric arc furnace. In actual production, a variety of carbonaceous reducing agents (petroleum coke, charcoal, coal, etc.) will be reasonably mixed and formulated so that different materials can be fully burned and utilized. In my country's coal resource production and reserves, high-quality anthracite and coking coal account for a relatively low proportion, while low-rank coal with high volatile content is abundant, accounting for about 48% of China's coal resource reserves. Low-rank coal is a low-value resource in industrial silicon smelting, with extremely low utilization rate and low price. It is of great significance to study how low-rank coal can be more effectively used in industrial silicon smelting.
[0003] Carbonaceous reducing agents account for 25%-30% of the production cost in the industrial silicon industry. Currently, low-rank coal is not used in large proportion in the industrial silicon industry, mainly because compared with existing carbonaceous reducing agents such as charcoal, petroleum coke and clean coal, its fixed carbon content is relatively low, its volatile matter is high, and its adhesion is weak. The production cost of low-rank non-sticky or weakly sticky coal is extremely low. If it can be optimized and improved to meet the furnace requirements for industrial silicon smelting and replace some of the existing carbonaceous reducing agents, it will be of great significance to the efficient utilization of low-rank coal and the field of industrial silicon smelting. Low-rank coal is a low-value resource in industrial silicon smelting, with extremely low utilization rate and low price. It is of great significance to study how low-rank coal can be more effectively used in industrial silicon smelting.
[0004] Microsilica fume is the dust formed by the oxidation of Si and SiO gases in the flue and rapid condensation with air during the production of metallic silicon in industrial silicon ore furnaces. It is also called silica fume. The main chemical component of microsilica fume is SiO2, in which SiO2 mainly exists in non-crystalline phase (or amorphous SiO2), with a content of ≥80%, less impurities, and a specific surface area of 20-28m 2 / g, more than 80% of the particles are smaller than 10μm, with high chemical activity, easy to react with alkali, and light weight, high refractoriness, strong activity, etc. In recent years, with the strengthening of environmental protection efforts, the output of microsilica fume has increased year by year. If it is directly discharged or dumped, it will cause environmental pollution and waste of resources. At present, the utilization rate of microsilica fume is less than one-third. From the perspective of cost saving, returning microsilica fume to the smelting process of the submerged arc furnace is one of the simplest and easiest options to reduce economic losses.
[0005] At present, there is little utilization of low-rank non-caking coal. Patent 202211156507.7 mixes biomass binder and low-rank non-caking coal powder, and at the same time, alkali metal or alkaline earth metal solution, water and inorganic binder solution are uniformly sprayed onto the mixed material in sequence, and then cold-pressed to obtain pellets, low-temperature roasted under oxygen-free conditions, and cooled to room temperature with the furnace to obtain composite carbonaceous reducing agent pellets for industrial silicon smelting. Since carbonaceous reducing agents have strict requirements on ash content, and biomass binders have high ash content, this is not conducive to the subsequent smelting of industrial silicon. Patent CN202311453081.6 uses different bonding coals to coat charcoal powder, petroleum coke and low-rank non-caking coal, and then presses them into pellets with water, binder and alkali metal additives, and finally prepares them by microwave roasting. However, this method makes less use of low-rank non-caking coal, and only the inner layer of low-rank non-caking coal is used, and the utilization rate is low. At present, there are no patents or papers that directly combine low-rank non-caking coal and microsilicon powder to prepare carbonaceous reducing agent pellets for industrial silicon smelting. At the same time, the composite organic binder selected by the present invention avoids the introduction of impurity elements such as Fe, Al, Ca, P, Ti and B. In order to actively respond to the green development of traditional energy and realize the "waste to treasure" of low-value resources, the efficient utilization of resources in the smelting process is of great practical significance for reducing the production cost of industrial silicon, improving the efficiency of resource and energy utilization and environmental protection. Summary of the invention
[0006] In view of the problem of low utilization rate of low-rank non-caking coal and micro-silicon powder in the prior art, the present invention proposes a carbonaceous reducing agent pellet with low-rank non-caking coal as the main body and its application. Specifically, it includes a carbonaceous reducing agent pellet with low-rank non-caking coal as the main body coupled with micro-silicon powder, its preparation method and its application in industrial silicon smelting. The carbonaceous reducing agent pellet for industrial silicon described in the present invention mainly uses low-rank non-caking coal as the main carbonaceous material, and is mixed evenly with a composite organic binder and micro-silicon powder to obtain a mixed material A; the reinforcing agent is added to water to make it a wetting medium, and then added to the mixed material A for wet grinding and mixing to obtain a mixed material B; then it is placed under a pressure of 10-20MPa to press and shape to obtain a cylindrical pellet precursor C; then the pellet precursor C is placed in a microwave tube furnace with argon gas, and roasted at a temperature of 450-650℃ for 60-90min, and cooled to room temperature with the furnace to obtain the carbonaceous reducing agent pellet for industrial silicon. The composite organic binder is mainly composed of starch and a tackifier, wherein the tackifier is composed of at least sodium carboxymethyl cellulose and hydroxypropyl cellulose for improving thermoplasticity and one or more of two major categories, namely sodium lignin sulfonate, sodium dodecylbenzene sulfonate, polyacrylamide and sodium humate for improving surface activity and formability; the reinforcing agent is mainly composed of one or two of sodium hydroxide and potassium hydroxide in combination with an alkali metal additive. The pellets prepared by the present invention have the characteristics of high fixed carbon content, high pellet strength, high anti-crushing rate, good static spherical index, low introduced impurity content and high reactivity. Low-grade non-sticky coal is applied in large proportion, and the microsilicon powder produced by the ore-fired furnace is recycled. At the same time, it is clean and environmentally friendly, and can be fully used for the smelting and production of industrial silicon, reducing the smelting unit consumption and production costs. It can replace or partially replace charcoal as a carbonaceous reducing agent for industrial silicon smelting.
[0007] The present invention discloses a carbonaceous reducing agent pellet with low-rank non-caking coal as the main component, and the preparation of the carbonaceous reducing agent pellet comprises the following steps:
[0008] (1) crushing and grinding the dried low-rank non-caking coal to a particle size of less than 5 mm, with the particle size of 1-3 mm accounting for 30-60%, to obtain micro-spherical particles of the low-rank non-caking coal; the low-rank non-caking coal has a caking index of less than 50, which of course includes non-caking coal with a caking index of less than 5, preferably non-caking coal with a caking index of less than 2;
[0009] (2) Using micro-spherical particles of low-rank non-caking coal as the main carbonaceous material of pellets, adding a composite organic binder and microsilica powder, and then mixing them evenly to obtain a mixture A with an average particle size of 0.75-1.5 mm; the composite organic binder is composed of D and a bonding agent, the SiO2 in the microsilica powder is greater than 80wt% and the particle size is less than 1.5 mm; the D is a polysaccharide and / or a polysaccharide polymer; the bonding agent is selected from at least one of lignin sulfonate, dodecylbenzene sulfonate, polyacrylamide, and humate;
[0010] (3) adding a reinforcing agent to water to prepare an alkali solution wetting medium containing an alkali metal additive, and then adding the reinforcing agent to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B having an average particle size of 0.5-1 mm; the reinforcing agent is an alkaline substance containing an alkali metal element;
[0011] (4) Pressing the mixed material B under a pressure of 10 to 20 MPa to obtain a precursor C;
[0012] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 450 to 650° C., and then cooled to room temperature in the furnace to obtain the carbonaceous reducing agent pellets for industrial silicon.
[0013] Preferably, the drying temperature of the low-rank non-caking coal is 105-110°C for 12-36 hours.
[0014] In the step (1), the fixed carbon content of the low-rank caking-free coal is ≥55wt.%, the ash content is <5wt.%, and the caking index n is less than or equal to 1, which of course includes a caking index of 0.
[0015] In the step (2), the proportion of low-rank non-caking coal as the main carbonaceous material in the mixed material A is 84-92wt.%, the added amount of the composite organic binder is 4-8wt.%, and the added amount of microsilica powder is 4-8wt.%.
[0016] In the step (2), the composite organic binder is composed of starch and a tackifier, wherein the added proportion of starch in the composite organic binder is 50-65wt.%, and the rest is the tackifier; the tackifier is composed of at least one or more of sodium carboxymethyl cellulose and hydroxypropyl cellulose for improving thermoplasticity and sodium lignin sulfonate, sodium dodecylbenzene sulfonate, polyacrylamide and sodium humate for improving surface activity and formability; wherein the tackifier for improving thermoplasticity accounts for 10-20wt.% of the total mass of the composite organic binder, and the tackifier for improving surface activity and formability accounts for 25-30wt.% of the total mass of the composite organic binder.
[0017] As a further preference, if two types of adhesion promoters (ie, adhesion promoters for improving thermoplasticity and adhesion promoters for improving surface activity and formability) appear in multiple combinations, the proportions of various organic substances in the same type of adhesives are the same.
[0018] The microsilica powder in step (2) is taken from the flue of the submerged arc furnace, with a SiO2 content of 85-95% and a mass density of 500-670 kg / m 2 .
[0019] In step (3), the enhancer is mainly composed of one or two of sodium hydroxide and potassium hydroxide and an alkali metal additive, and the alkali metal additive is one or more of K2CO3, Na2CO3 and NaHCO3 powder; the addition ratio of the alkali liquid wetting medium is 8-12wt.% of the mixed material A.
[0020] In the step (3), the addition ratios of hydroxide, alkali metal additive and water in the alkaline solution wetting medium are 4-6wt.%, 6-9wt.% and 85-90wt.%, respectively. If the hydroxide and alkali metal additive are not of the same kind, the ratios of each kind are the same.
[0021] In the step (4), the mixed material B is placed under a pressure of 10 to 20 MPa and pressed to obtain a cylindrical pellet precursor C with a diameter of 60 to 70 mm and a height of 85 to 100 mm.
[0022] In the step (5), the microwave roasting time is 60 to 90 minutes, and the microwave power is 3 to 5 kW.
[0023] The final pellets in step (5) have a fixed carbon content of ≥70wt.%, a cold pressing strength of ≥12MPa, a crushing resistance of ≥85%, a hot pressing strength of ≥8MPa, a static sphericity index of ≥0.7, and a reaction activity of ≥90% at a temperature of 1100°C.
[0024] The carbonaceous reducing agent pellets disclosed by the present invention are used for silicon smelting, including industrial silicon smelting.
[0025] Selection principle of binder: During the production of industrial silicon, the impurity content in the raw materials is strictly controlled. During the refining process of industrial silicon, the oxide of Na will be reduced to a gaseous metal element at about 1000°C and escape, so the Na element is not specified in the binder. Although Al, Ca, P, Ti and B can be reduced by refining methods, the maximum removal efficiency is only 70%, so the binder cannot contain a large amount of elements such as Al, Ca, P, Ti and B. At present, there is no effective removal method for the Fe element, so the control of the Fe element in the raw materials in industrial silicon production is the most stringent, and the Fe content in the raw materials is required to be as low as possible. The composite organic binder selected by the present invention is composed of a starch main body and a viscosity promoter, and does not involve elements such as Fe, Al, Ca, P, Ti and B.
[0026] The relevant principles involved between the enhancer, microsilica powder and composite organic binder: the addition of alkali metal additives in the enhancer will promote the structural rearrangement and crystallization effect of low-order non-caking coal, increase the porosity, and then increase the contact area, thereby improving the reaction efficiency. At the same time, K and Na will also promote industrial silicon smelting; at the same time, the hydroxide in the enhancer combines with water to form alkali solution, which will modify the starch and adhesion promoter in the composite organic binder, react with the organic matter therein, change the physical and chemical properties of the organic matter, and change the chemical structure to generate new chemical bonds and functional groups. In addition, the alkali solution can also neutralize the protons in the reaction system, act as an acid binder, activate molecular ions, and generate negative charges at the same time. The mutual repulsion of like charges causes the molecules to straighten to form a network structure, thereby locking in moisture and increasing its interaction with water molecules. After the alkali solution combines with water molecules, the curled molecules are untied to form a network structure. These changes help to improve the bonding properties of the binder. Silica fume is finer. After adding silica fume to the pellets, the intermolecular movement is stronger, which strengthens the migration of atoms and the binding force between particles, promoting the fusion of all particles inside the pellets and greatly increasing the degree of aggregation of the network structure inside the pellets. In addition, there are a large number of irregularly structured molecules and atoms on the surface of silica fume particles, which are highly chemically active and have a strong reaction ability with alkali solution (nSiO2+2NaOH→Na2O·nSiO2+H2O), among which Na2O·nSiO2 is the main component of water glass and is a gel. In addition, excessive silica fume can fill the tiny pores of the microsphere particles, which can improve the comprehensive performance of the pellets.
[0027] The beneficial effects of the present invention are:
[0028] (1) The present invention utilizes low-rank non-caking coal resources on a large scale and efficiently, expands the scope of coal used for coking, and can effectively alleviate the contradiction between the shortage of some resources and the direct industrial production needs and economic development. At the same time, from the perspective of cost saving, the microsilica powder comes directly from the silicon factory. Returning the microsilica powder to the smelting process of the submerged arc furnace is one of the simplest and easiest options to reduce economic losses, thereby realizing the recovery and regeneration of microsilica powder resources.
[0029] (2) The fine particles of microsilica powder result in a large number of voids inside the pellets, which is beneficial to reduce the burn-out rate during smelting, ensure the efficient use of carbonaceous materials, and appropriately improve the stability of combustion. At the same time, it can improve the bonding performance and high-temperature consolidation performance when combined with alkali solution. The re-entry of microsilica powder into the furnace can increase the recovery rate of silica, reduce silica consumption, and reduce production costs.
[0030] (3) The high volatile matter of the reinforcing agent and low-rank non-caking coal can increase the porosity of the pellets and the reaction activity after microwave roasting and activation. At the same time, microwave-assisted roasting of the pellets causes the dielectric loss of the carbon material to heat the carbon material as a whole to the sintering temperature to achieve densification and thus improve the strength of the pellets. At the same time, the intake of alkali metals K and Na plays an important role in saving smelting power consumption, reducing process energy consumption, improving the production efficiency of the submerged arc furnace, reducing SiC furnace top deposition and slowing down the rise of the furnace bottom;
[0031] (4) The composite organic binder in the present invention has the characteristics of long-chain molecules and high viscosity after hydration. The main starch can be modified in combination with alkali solution to improve the bonding ability, while avoiding the introduction of impurity elements such as Fe, Al, Ca, P, Ti and B, which is conducive to bonding fine-grained powder into agglomerates, reducing the amount of binder used and the introduction of impurities, and can increase the low-temperature strength of the pellets at low temperatures. It has good stability at high temperatures and acts as a pellet skeleton under high temperature conditions, weakening the adverse effects of the decrease in pellet strength due to the burnout of organic matter. At the same time, it fully considers the characteristics of industrial silicon smelting, reduces unnecessary impurities, and inhibits the pulverization of powder agglomerates in the ore-fired furnace, further improving the utilization rate of resources;
[0032] (5) The present invention adopts wet grinding mixing. During the grinding process, the wetting medium can effectively penetrate and promote the combination of powders, increase the contact area and improve the porosity, so that the mixed carbon material has higher reaction activity and improves the reaction efficiency of industrial silicon smelting. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The figures are the actual pictures of the precursor and the calcined product in Examples 1, 2 and Comparative Example 1;
[0034] Figure 2 Actual picture of the pellets being sealed with wax.
[0035] Figure 1 The white and grayish white parts on the surface of the pellets are composite organic binders and microsilica powder. Figure A is the pellet precursor obtained in step 4 of Example 1, Figure B is the precursor obtained in step 4 of Comparative Example 1, and the pellets on the left and right sides of Figure C are the pellet precursor obtained in step 4 of Example 2 and the carbonaceous reducing agent pellets for industrial silicon obtained after microwave roasting in step 5. It can be found that the pellets are significantly smaller after roasting, and the fixed carbon content of the pellets is increased, which is caused by the escape of volatiles; at the same time, some substances in the composite organic binder are carbonized, which also makes the fixed carbon content in the comparative example containing the composite organic binder higher than that without the composite organic binder under the same conditions.
[0036] from Figure 2 The basic situation of the ball when the wax sealing method is used can be seen in the figure. DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.
[0038] The microsilica powder described in the embodiment of the present invention is taken from the flue of a submerged arc furnace in a silicon factory in Yunnan. The SiO2 content is 91% and the mass density is 617kg / m 2 .
[0039] In the present invention, the fixed carbon content of the carbonaceous reducing agent pellets is measured according to GB / T 212-2008, and the mass percentage of water, volatile matter and ash is measured first, and then the mass percentage of the three is subtracted from 100% to obtain the mass percentage of the fixed carbon.
[0040] In the present invention, the reaction activity at 1100°C is measured according to GB / T 220-2001. The pellets are firstly dry-distilled to remove volatiles. Then they are placed in a reaction tube for heating, and a certain flow of carbon dioxide is introduced to react with the pellets. The content of carbon dioxide in the gas after the reaction is measured, and the percentage of the amount of carbon dioxide reduced to carbon monoxide in the amount of carbon dioxide introduced, i.e., the carbon dioxide reduction rate (%), is used as an index of the chemical reactivity of the pellets.
[0041] In the present invention, the crushing resistance of the pellets is tested according to GB / T 15459-1995. The pellets are dropped from a height of 2m onto a 3mm thick steel plate for three times, and then sieved with a sieve with an aperture of 25mm. The mass of the fragments on the sieve is weighed, and the mass of the fragments on the sieve is divided by the total mass of the pellets and multiplied by 100%, which is the crushing resistance.
[0042] In the present invention, the cold compression strength is obtained by drying the pressed pellets at 100°C to remove moisture, and then placing the pellets on a strength testing machine. The testing machine applies pressure to the pellets at a uniform speed until the pellets break. The maximum value of the pressure on the testing machine is the cold compression strength of the pellets.
[0043] In the present invention, the hot pressing strength is obtained by placing the pressed pellets in an atmosphere furnace at 800°C for 1 hour, while introducing an inert gas such as Ar into the furnace. After the heat preservation is completed, the pellets are taken out, and after the pellets are cooled to room temperature, they are placed on a strength measurement tester. The tester applies pressure to the pellets at a uniform speed until the pellets break. The maximum value of the pressure on the tester is the hot pressing strength of the pellets.
[0044] In the present invention, the static sphericity index K is a parameter that comprehensively reflects the particle size, particle size composition, specific surface area and hydrophilicity of the material, and is calculated using the maximum molecular water / (maximum capillary water-maximum molecular water).
[0045] The maximum molecular water of the pellets is measured by filter pressing. The pellet powder sample is moistened with water to saturation and left to stand for 2 hours to allow the particle surface to be fully moistened. Then the lower pressure plug is placed in the mold, and 20 filter papers with a diameter of 60 mm are placed on the lower pressure plug. The prepared pellet powder sample is placed on the filter paper in the pressure mold and laid flat. The pressure mold with the sample is placed on the hydraulic press at 65 kg / cm 2 The pressure is applied for 5 minutes, and the sample is taken out and weighed to obtain G1. Then the sample is dried at 110°C to constant weight to obtain G2. The maximum molecular water can be calculated using (G1-G2) / G1*100%.
[0046] The maximum capillary water of the pellets is measured by the volumetric method and the wax sealing method. The mass of the dried pellets is recorded as G3, and placed in a beaker with paraffin wax to ensure that the paraffin wax can cover the pellets. The beaker is heated to allow the paraffin wax to enter the pellets through the pores. The pellets are taken out when no bubbles are generated on the surface of the pellets, and weighed after cooling to room temperature as G4. The density of water and paraffin wax is used for conversion, and the mass of water is G5. The maximum capillary water of the pellets can be obtained by calculation using G5 / (G5-G3)*100%. The reason why the saturated water method cannot be used here but the wax sealing method must be used is that the main body of the pellets is low-order non-sticky coal, which has porous water absorption. It is subjected to the impact and pressure of water in water, and the internal structure cannot remain stable, resulting in the fall apart of the pellets.
[0047] Example 1: A method for preparing carbonaceous reducing agent pellets with low-rank non-caking coal as the main component coupled with micro-silicon powder for industrial silicon smelting, the specific steps are as follows:
[0048] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, with a particle size of 1-3 mm accounting for 30%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 59.14wt.%, the ash content is 4.07wt.%, and the rest is volatile matter, and the caking index n is 0;
[0049] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 0.75 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 92wt.%, the addition amount of the composite organic binder is 4wt.%, and the addition amount of microsilica powder is 4wt.%.
[0050] The composite organic binder is composed of starch and a tackifier, wherein the added proportion of starch is 55wt.%, and the rest is the tackifier; the tackifier is composed of 17wt.% of sodium carboxymethyl cellulose for improving thermoplasticity and 28wt.% of sodium dodecylbenzene sulfonate for improving surface activity and formability;
[0051] (3) 6 wt.% of sodium hydroxide, 9 wt.% of K2CO3 and 85 wt.% of water are prepared into an alkali solution wetting medium. Based on 100 wt.% of the mixed material A, 8 wt.% of the alkali solution wetting medium is added to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B with an average particle size of 0.5 mm;
[0052] (4) Pressing the mixed material B under a pressure of 10 MPa to obtain a cylindrical pellet precursor C with a diameter of 60 mm and a height of 90 mm;
[0053] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 450° C., a roasting time of 90 min, and a microwave power of 4 kW. The pellet is then cooled to room temperature to obtain the carbonaceous reducing agent pellet for industrial silicon.
[0054] The carbonaceous reducing agent pellets prepared in this example have a fixed carbon content of 72.37 wt.%, a cold pressing strength of 12.24 MPa, a crushing resistance of 87.64%, a hot pressing strength of 8.97 MPa, a static sphericity index of 0.72, and a reaction activity of 92.74% at a temperature of 1100°C.
[0055] Comparative Example 1: This comparative example differs from Example 1 in that: no microsilica powder and composite organic binder are added;
[0056] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 71.24wt.%, a cold pressing strength of 10.56MPa, an anti-crushing rate of 80.12%, a hot pressing strength of 5.61MPa, a static sphericity index of 0.25, and a reaction activity of 81.25% at a temperature of 1100°C.
[0057] Comparative Example 2: This comparative example differs from Example 1 in that: no microsilica powder and reinforcing agent are added;
[0058] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 71.98wt.%, a cold pressing strength of 10.91MPa, an anti-crushing rate of 81.57%, a hot pressing strength of 6.14MPa, a static sphericity index of 0.34, and a reaction activity of 83.56% at a temperature of 1100°C.
[0059] Example 2: A method for preparing carbonaceous reducing agent pellets with low-rank non-caking coal as the main component coupled with micro-silicon powder for industrial silicon smelting, the specific steps are as follows:
[0060] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, wherein the particle size of 1-3 mm accounts for 60%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 58.91wt.%, the ash content is 4.13wt.%, and the rest is volatile matter, and the caking index n is 0;
[0061] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 90wt.%, the addition amount of the composite organic binder is 6wt.%, and the addition amount of microsilica powder is 4wt.%.
[0062] The composite organic binder is composed of starch and a viscosity enhancer, wherein the added proportion of starch is 50wt.%, and the rest is the viscosity enhancer; the viscosity enhancer is composed of 20wt.% of hydroxypropyl cellulose for improving thermoplasticity and 30wt.% of polyacrylamide for improving surface activity and formability;
[0063] (3) 5 wt.% of sodium hydroxide, 7 wt.% of NaHCO3 and 88 wt.% of water are prepared into an alkali solution wetting medium. Based on 100 wt.% of the mixed material A, 10 wt.% of the alkali solution wetting medium is added to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B with an average particle size of 0.6 mm;
[0064] (4) Pressing the mixed material B under a pressure of 15 MPa to obtain a cylindrical pellet precursor C with a diameter of 64 mm and a height of 85 mm;
[0065] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 650° C., a roasting time of 60 min, and a microwave power of 4 kW. The pellet is then cooled to room temperature to obtain the carbonaceous reducing agent pellet for industrial silicon.
[0066] The carbonaceous reducing agent pellets prepared in this example have a fixed carbon content of 72.15 wt.%, a cold pressing strength of 12.77 MPa, a crushing resistance of 89.21%, a hot pressing strength of 9.11 MPa, a static sphericity index of 0.78, and a reaction activity of 93.45% at a temperature of 1100°C.
[0067] Comparative Example 3: This comparative example differs from Example 2 in that: no microsilica powder and composite organic binder are added;
[0068] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 70.17wt.%, a cold pressing strength of 10.89MPa, an anti-crushing rate of 81.76%, a hot pressing strength of 5.81MPa, a static sphericity index of 0.27, and a reaction activity of 81.69% at a temperature of 1100°C.
[0069] Comparative Example 4: This comparative example differs from Example 2 in that: no microsilica powder and reinforcing agent are added;
[0070] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 70.45wt.%, a cold pressing strength of 11.21MPa, an anti-crushing rate of 83.69%, a hot pressing strength of 6.07MPa, a static sphericity index of 0.37, and a reaction activity of 83.74% at a temperature of 1100°C.
[0071] Example 3: A method for preparing carbonaceous reducing agent pellets with low-rank non-caking coal as the main component coupled with micro-silicon powder for industrial silicon smelting, the specific steps are as follows:
[0072] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, wherein the particle size of 1-3 mm accounts for 40%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 55.74wt.%, the ash content is 4.81wt.%, and the rest is volatile matter, and the caking index n is 0;
[0073] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1.2 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 87wt.%, the addition amount of the composite organic binder is 7wt.%, and the addition amount of microsilica powder is 6wt.%.
[0074] The composite organic binder is composed of starch and a tackifier, wherein the added proportion of starch is 58wt.%, and the rest is the tackifier; the tackifier is composed of 15wt.% of sodium carboxymethyl cellulose for improving thermoplasticity and 27wt.% of sodium lignin sulfonate for improving surface activity and formability;
[0075] (3) 4 wt.% of sodium hydroxide, 6 wt.% of Na2CO3 and 90 wt.% of water are prepared into an alkali solution wetting medium. Based on 100 wt.% of the mixed material A, 12 wt.% of the alkali solution wetting medium is added to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B with an average particle size of 0.75 mm;
[0076] (4) Pressing the mixed material B under a pressure of 15 MPa to obtain a cylindrical pellet precursor C with a diameter of 70 mm and a height of 100 mm;
[0077] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 550° C., a roasting time of 80 min, and a microwave power of 5 kW. The pellet is then cooled to room temperature to obtain the carbonaceous reducing agent pellet for industrial silicon.
[0078] The carbonaceous reducing agent pellets prepared in this example have a fixed carbon content of 70.49wt.%, a cold pressing strength of 12.98MPa, a crushing resistance of 90.45%, a hot pressing strength of 8.83MPa, a static sphericity index of 0.81, and a reaction activity of 91.89% at a temperature of 1100°C.
[0079] Comparative Example 5: This comparative example differs from Example 3 in that: no microsilica powder and composite organic binder are added;
[0080] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 68.53wt.%, a cold pressing strength of 11.27MPa, an anti-crushing rate of 82.06%, a hot pressing strength of 6.49MPa, a static sphericity index of 0.29, and a reaction activity of 81.98% at a temperature of 1100°C.
[0081] Comparative Example 6: This comparative example differs from Example 3 in that: no microsilica powder and reinforcing agent are added;
[0082] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 68.94wt.%, a cold pressing strength of 11.49MPa, an anti-crushing rate of 82.98%, a hot pressing strength of 6.87MPa, a static sphericity index of 0.38, and a reaction activity of 83.47% at a temperature of 1100°C.
[0083] Example 4: A method for preparing carbonaceous reducing agent pellets with low-rank non-caking coal as the main component coupled with micro-silicon powder for industrial silicon smelting, the specific steps are as follows:
[0084] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, wherein the particle size of 1-3 mm accounts for 50%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 57.82 wt.%, the ash content is 4.54 wt.%, and the rest is volatile matter, and the caking index n is 0;
[0085] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1.5 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 84wt.%, the addition amount of the composite organic binder is 8wt.%, and the addition amount of microsilica powder is 8wt.%.
[0086] The composite organic binder is composed of starch and adhesive, wherein the added proportion of starch is 65wt.%, and the rest is adhesive; the adhesive is composed of 10wt.% of hydroxypropyl cellulose for improving thermoplasticity and a total of 25wt.% of sodium lignin sulfonate and sodium dodecylbenzene sulfonate (each accounting for 12.5wt.%) for improving surface activity and formability;
[0087] (3) 5 wt.% of sodium hydroxide, 4 wt.% of K2CO3, 4 wt.% of NaHCO3 and 87 wt.% of water are prepared into an alkali solution wetting medium. Based on 100 wt.% of the mixed material A, 11 wt.% of the alkali solution wetting medium is added to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B with an average particle size of 1 mm.
[0088] (4) Pressing the mixed material B under a pressure of 20 MPa to obtain a cylindrical pellet precursor C with a diameter of 68 mm and a height of 95 mm;
[0089] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 600° C., a roasting time of 70 min, and a microwave power of 3 kW. The pellet is then cooled to room temperature to obtain the carbonaceous reducing agent pellet for industrial silicon.
[0090] The carbonaceous reducing agent pellets prepared in this example have a fixed carbon content of 71.84wt.%, a cold pressing strength of 13.11MPa, a crushing resistance of 91.78%, a hot pressing strength of 8.27MPa, a static sphericity index of 0.74, and a reaction activity of 91.27% at a temperature of 1100°C.
[0091] Comparative Example 7: This comparative example differs from Example 4 in that: no microsilica powder and composite organic binder are added;
[0092] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 69.84wt.%, a cold pressing strength of 11.21MPa, an anti-crushing rate of 81.85%, a hot pressing strength of 6.17MPa, a static sphericity index of 0.31, and a reaction activity of 82.46% at a temperature of 1100°C.
[0093] Comparative Example 8: This comparative example differs from Example 4 in that no microsilica powder and reinforcing agent are added;
[0094] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 70.28wt.%, a cold pressing strength of 11.69MPa, an anti-crushing rate of 83.69%, a hot pressing strength of 6.59MPa, a static sphericity index of 0.40, and a reaction activity of 84.15% at a temperature of 1100°C.
[0095] Example 5: A method for preparing carbonaceous reducing agent pellets with low-rank non-caking coal as the main component coupled with micro-silicon powder for industrial silicon smelting, the specific steps are as follows:
[0096] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, wherein the particle size of 1-3 mm accounts for 55%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 56.89wt.%, the ash content is 4.61wt.%, and the rest is volatile matter, and the caking index n is 0;
[0097] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1.2 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 85wt.%, the addition amount of the composite organic binder is 8wt.%, and the addition amount of microsilica powder is 7wt.%.
[0098] The composite organic binder is composed of starch and adhesives, wherein the added proportion of starch is 60wt.%, and the rest is adhesives; the adhesives are composed of 13wt.% of sodium carboxymethyl cellulose and hydroxypropyl cellulose (each of which accounts for 6.5wt.%) for improving thermoplasticity and 27wt.% of sodium dodecylbenzene sulfonate, polyacrylamide and sodium humate (each of which accounts for 9wt.%) for improving surface activity and formability;
[0099] (3) 2 wt.% of sodium hydroxide, 2 wt.% of potassium hydroxide, 4 wt.% of Na2CO3, 4 wt.% of NaHCO3 and 88 wt.% of water are prepared into an alkali solution wetting medium, and based on 100 wt.% of the mixed material A, 11 wt.% of the alkali solution wetting medium is added to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B with an average particle size of 0.65 mm;
[0100] (4) Pressing the mixed material B under a pressure of 18 MPa to obtain a cylindrical pellet precursor C with a diameter of 66 mm and a height of 93 mm;
[0101] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 620° C., a roasting time of 70 min, and a microwave power of 4 kW. The pellet is then cooled to room temperature to obtain the carbonaceous reducing agent pellet for industrial silicon.
[0102] The carbonaceous reducing agent pellets prepared in this example have a fixed carbon content of 70.94wt.%, a cold pressing strength of 13.03MPa, a crushing resistance of 92.14%, a hot pressing strength of 8.73MPa, a static sphericity index of 0.76, and a reaction activity of 93.49% at a temperature of 1100°C.
[0103] Comparative Example 9: The difference between this comparative example and Example 5 is that no microsilica powder and composite organic binder are added.
[0104] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 68.68wt.%, a cold pressing strength of 10.95MPa, an anti-crushing rate of 82.24%, a hot pressing strength of 5.98MPa, a static sphericity index of 0.33, and a reaction activity of 82.15% at a temperature of 1100°C.
[0105] Comparative Example 10: This comparative example differs from Example 5 in that no microsilica powder and reinforcing agent are added.
[0106] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 69.65wt.%, a cold pressing strength of 11.26MPa, an anti-crushing rate of 84.12%, a hot pressing strength of 6.31MPa, a static sphericity index of 0.42, and a reaction activity of 84.56% at a temperature of 1100°C.
[0107] Example 6: A method for preparing carbonaceous reducing agent pellets with low-rank non-caking coal as the main component coupled with micro-silicon powder for industrial silicon smelting, the specific steps are as follows:
[0108] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, wherein the particle size of 1-3 mm accounts for 55%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 59.68wt.%, the ash content is 3.97wt.%, and the rest is volatile matter, and the caking index n is 0;
[0109] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1.3 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 86wt.%, the addition amount of the composite organic binder is 8wt.%, and the addition amount of microsilica powder is 6wt.%.
[0110] The composite organic binder is composed of starch and adhesives, wherein the added proportion of starch is 54wt.%, and the rest is adhesives; the adhesives are composed of 14wt.% of sodium carboxymethyl cellulose and hydroxypropyl cellulose (each of which accounts for 7wt.%) for improving thermoplasticity, and 32wt.% of sodium lignin sulfonate, sodium dodecylbenzene sulfonate, polyacrylamide and sodium humate (each of which accounts for 8wt.%) for improving surface activity and formability;
[0111] (3) 6 wt.% of sodium hydroxide, 3 wt.% of Na2CO3, 3 wt.% of K2CO3, 3 wt.% of NaHCO3 and 85 wt.% of water are prepared into an alkali solution wetting medium, and 12 wt.% of the alkali solution wetting medium is added to the mixed material A based on 100 wt.% of the mixed material A, and wet-grinded and mixed to obtain a mixed material B with an average particle size of 0.55 mm;
[0112] (4) Pressing the mixed material B under a pressure of 20 MPa to obtain a cylindrical pellet precursor C with a diameter of 70 mm and a height of 98 mm;
[0113] (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 640° C., a roasting time of 65 min, and a microwave power of 4 kW. The pellet is then cooled to room temperature to obtain the carbonaceous reducing agent pellet for industrial silicon.
[0114] The carbonaceous reducing agent pellets prepared in this example have a fixed carbon content of 72.58 wt.%, a cold pressing strength of 13.37 MPa, a crushing resistance of 92.87%, a hot pressing strength of 8.95 MPa, a static sphericity index of 0.82, and a reaction activity of 94.38% at a temperature of 1100°C.
[0115] Comparative Example 11: This comparative example differs from Example 6 in that no microsilica powder and composite organic binder are added.
[0116] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 70.68wt.%, a cold pressing strength of 11.19MPa, an anti-crushing rate of 81.64%, a hot pressing strength of 6.27MPa, a static sphericity index of 0.31, and a reaction activity of 83.74% at a temperature of 1100°C.
[0117] Comparative Example 12: This comparative example differs from Example 6 in that no microsilica powder and reinforcing agent are added.
[0118] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 71.25wt.%, a cold pressing strength of 11.67MPa, an anti-crushing rate of 82.61%, a hot pressing strength of 6.38MPa, a static sphericity index of 0.41, and a reaction activity of 85.74% at a temperature of 1100°C.
[0119] Comparative Example 13: Other conditions are the same as those in Example 1, except that:
[0120] (1) crushing and grinding low-rank non-caking coal after vacuum drying at 110° C. for 24 hours to a particle size of less than 5 mm, with a particle size of 1-3 mm accounting for 30%, to obtain micro-spherical particles of low-rank non-caking coal; the fixed carbon content of the low-rank non-caking coal is 59.14wt.%, the ash content is 4.07wt.%, and the rest is volatile matter, and the caking index n is 0;
[0121] (2) The micro-spherical particles of low-rank non-caking coal are pressed under a pressure of 10 MPa to obtain a cylindrical pellet precursor with a diameter of 60 mm and a height of 90 mm;
[0122] (3) placing the pellet precursor in a microwave tube furnace into which argon gas is introduced, performing microwave roasting at a temperature of 450° C., a roasting time of 90 min, and a microwave power of 4 kW, and then cooling the furnace to room temperature to obtain the carbonaceous reducing agent pellets for industrial silicon.
[0123] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 75.19wt.%, a cold pressing strength of 10.32MPa, a crushing resistance of 79.89%, a hot pressing strength of 5.48MPa, a static sphericity index of 0.23, and a reaction activity of 80.46% at a temperature of 1100°C.
[0124] Comparative Example 14: Other conditions are the same as those in Example 1, except that:
[0125] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and an organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1.5 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 84wt.%, the addition amount of the organic binder is 8wt.%, and the addition amount of microsilica powder is 8wt.%.
[0126] The organic binder is starch;
[0127] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 71.89wt.%, a cold pressing strength of 12.99MPa, a crushing resistance of 91.08%, a hot pressing strength of 8.53MPa, a static sphericity index of 0.75, and a reaction activity of 87.46% at a temperature of 1100°C.
[0128] Example 7: Other conditions are the same as those in Example 1, except that:
[0129] (2) Low-order non-caking coal particles are used as the main carbonaceous material of the pellets, and a composite organic binder and microsilica powder are added, and then mixed evenly to obtain a mixture A with an average particle size of 1 mm; wherein the proportion of low-order non-caking coal in the main carbonaceous material is 90wt.%, the addition amount of the composite organic binder is 6wt.%, and the addition amount of microsilica powder is 4wt.%.
[0130] The composite organic binder is composed of starch and a viscosity enhancer, wherein the added proportion of starch is 50wt.%, and the rest is the viscosity enhancer; the viscosity enhancer is hydroxypropyl cellulose for improving thermoplasticity;
[0131] The carbonaceous reducing agent pellets prepared in this comparative example have a fixed carbon content of 72.18wt.%, a cold pressing strength of 12.85MPa, a crushing resistance of 90.98%, a hot pressing strength of 9.34MPa, a static sphericity index of 0.73, and a reaction activity of 88.88% at a temperature of 1100°C.
[0132] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A carbonaceous reducing agent pellet with low-rank non-caking coal as the main component, characterized by: The preparation of the carbonaceous reducing agent pellets comprises the following steps: (1) crushing and grinding the dried low-rank non-caking coal to a particle size of less than 5 mm, with the particle size of 1-3 mm accounting for 30-60%, to obtain micro-spherical particles of the low-rank non-caking coal; the low-rank non-caking coal has a caking index of less than 50, which of course includes non-caking coal with a caking index of less than 5, preferably non-caking coal with a caking index of less than 2; (2) Using micro-spherical particles of low-rank non-caking coal as the main carbonaceous material of pellets, adding a composite organic binder and microsilica powder, and then mixing them evenly to obtain a mixture A with an average particle size of 0.75-1.5 mm; the composite organic binder is composed of D and a bonding agent, the SiO2 in the microsilica powder is greater than 80wt% and the particle size is less than 1.5 mm; the D is a polysaccharide and / or a polysaccharide polymer; the bonding agent is selected from at least one of lignin sulfonate, dodecylbenzene sulfonate, polyacrylamide, and humate; (3) adding a reinforcing agent to water to prepare an alkali solution wetting medium containing an alkali metal additive, and then adding the reinforcing agent to the mixed material A for wet grinding and uniform mixing to obtain a mixed material B having an average particle size of 0.5-1 mm; the reinforcing agent is an alkaline substance containing an alkali metal element; (4) Pressing the mixed material B under a pressure of 10 to 20 MPa to obtain a precursor C; (5) The pellet precursor C is placed in a microwave tube furnace into which argon gas is introduced, and microwave roasted at a temperature of 450 to 650° C., and then cooled to room temperature in the furnace to obtain the carbonaceous reducing agent pellets for industrial silicon.
2. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: The drying temperature of low-rank non-caking coal is 105-110℃ for 12-36h.
3. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: In step (1), the fixed carbon content of the low-rank caking-free coal is ≥55wt.%, the ash content is <5wt.%, and the caking index n is less than or equal to 1, which of course includes a caking index of 0.
4. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: In step (2), the proportion of low-rank non-caking coal as the main carbonaceous material in the mixed material A is 84-92wt.%, the added amount of the composite organic binder is 4-8wt.%, and the added amount of microsilica powder is 4-8wt.%.
5. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: In step (2), the composite organic binder is composed of starch and a tackifier, wherein the added proportion of starch in the composite organic binder is 50-65wt.%, and the rest is the tackifier; the tackifier is composed of at least one or more of sodium carboxymethyl cellulose and hydroxypropyl cellulose for improving thermoplasticity and sodium lignin sulfonate, sodium dodecylbenzene sulfonate, polyacrylamide and sodium humate for improving surface activity and formability; wherein the tackifier for improving thermoplasticity accounts for 10-20wt.% of the total mass of the composite organic binder, and the tackifier for improving surface activity and formability accounts for 25-30wt.% of the total mass of the composite organic binder.
6. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: The microsilica powder in step (2) is taken from the flue of the submerged arc furnace, with a SiO2 content of 85-95% and a mass density of 500-670 kg / m 2 .
7. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: In step (3), the enhancer is mainly composed of one or both of sodium hydroxide and potassium hydroxide and an alkali metal additive, and the alkali metal additive is one or more of K2CO3, Na2CO3 and NaHCO3 powder; the addition ratio of the alkali liquid wetting medium is 8-12wt.% of the mixed material A.
8. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: In step (3), the addition ratios of hydroxide, alkali metal additive and water in the alkaline solution wetting medium are 4-6wt.%, 6-9wt.% and 85-90wt.%, respectively, wherein if the hydroxide and alkali metal additive are not of the same kind, the ratios of each kind are the same.
9. The carbonaceous reducing agent pellets based on low-rank non-caking coal according to claim 1 are characterized by: In step (5), the microwave roasting time is 60 to 90 minutes, and the microwave power is 3 to 5 kW.
10. An application of carbonaceous reducing agent pellets based on low-rank non-caking coal as claimed in any one of claims 1 to 9, characterized in that: The carbonaceous reducing agent pellets are used for silicon smelting.
Citation Information
Patent Citations
Semi-coke-containing reducing agent for silicon smelting and preparation method thereof
CN115340094A
Composite carbonaceous reducing agent pellet for industrial silicon and preparation method thereof
CN117448566A
High-purity composite binder for metallurgical pellets and use method of high-purity composite binder
CN114737055A
Reducing agent for industrial silicon smelting and preparation method thereof
CN118125448A
Method for preparing composite carbonaceous reducing agent pellets for industrial silicon through sludge wrapping
CN118580877A
Cited By
Carbonaceous reducing agent pellet mainly composed of low-rank non-caking coal, and use thereof
WO2026091492A1